STUDI LITERATUR: ANALISIS PENERAPAN MODEL PEMBELAJARAN PROBLEM-BASED LEARNING (PBL), PROJECT BASED LEARNING (PJBL) DAN DEEP LEARNING PADA GURU BIOLOGI DAN SISWA DI KELAS XII SMAN 1 LABUHAN DELI - Tarisya Afdania; Aqila Shabira Purba; Nada Ahwani; Novia Putri Ramadhana; Rizal Mukra; Widya Arwita (Jurnal Bionatural, 2025)
This study aims to analyze the application of three innovative learning models, namely Problem-Based Learning (PBL), Project-Based Learning (PJBL), and Deep Learning, to Biology teachers and grade XII students at SMAN 1 Labuhan Deli. The background of this study is the need for more effective learning methods to improve student engagement, deep understanding, and critical thinking skills. The study used a descriptive qualitative approach with data collection techniques in the form of questionnaires given to teachers and students. The results showed that teachers appreciated the PJBL method more, which was considered effective in developing 21st century skills, such as collaboration and creativity, with the highest score of 40%. Meanwhile, students showed a balanced preference between PBL and PJBL, each scoring 34%, reflecting the flexibility and support of both methods for understanding the material through solving real problems. Deep Learning was considered effective by teachers in improving students' analytical skills, but received the lowest score from students (32%). The conclusion of this study emphasizes the need for a flexible approach in the application learning models to accommodate differences in perception and needs between teachers and students in order to optimally improve learning outcomes.